Penerapan Hukum Progresif dalam Penegakan Hukum di tengah Krisis Demokrasi - Yanto Sufriadi (Jurnal Hukum IUS QUIA IUSTUM, 2010)
This research is focused on the impact of globalization within the justice, welfare, and democracy, as well as to the question about what kind of law that is possible to create the justice and the welfare in the middle of democracy crisis is and also the question about how to apply that in Indonesia’s court. This study uses socio-legal approach which is mainly committing a quantitative method, based on the literature data. By using socio-legal approach, this study will conduct two kind approaches, which are social and normative juridical. This research makes claim that the globalization has finally made an impact to the happen of economy discriminatory and the widen case of poverty. Poverty will lead a bad impact to the democracy. In a situation of elitist legislation product, the settlement of law that is based on the legalpositivism tradition, it will give impact to the spread of discrimination and poverty. Because of it, in the middle of elitism legislation product, the progressive application of law can be considered as the alternative way to bring out the justice and the welfare for the people. The practice of Indonesia’s court has shown its development to the law’s progressive movement, nevertheless, the legal-positivism mainstream is still laid on several judges.Keywords : Globalization, democracy, justice, progressive law